Total Synthesis and Structural Validation of Phosdiecin A via Asymmetric Alcohol-Mediated Carbonyl Reductive Coupling - Della Felice, Franco (2019)
The first total synthesis and structural validation of phosdiecin A was accomplished in 13 steps through asymmetric iridium-catalyzed alcohol-mediated carbonyl reductive coupling. The present route is the shortest among >30 total and formal syntheses of fostriecin family members.